Possibilities at the Polar beamline with APS-U. Issue 1 (1st December 2022) - Strempfer, J; Kearney, S; Khan, A; Capatina, D; Reininger, R; Shu, D; Wolford, C; Golebiowski, M; Rebuffi, L; Shi, X; Kołodziej, T; Huang, X; et al.
Abstract: The Polar beamline will make use of the small emittance of the new APS-U storage ring and will offer extremely brilliant and coherent beam of variable polarization in the hard x-ray range. Tailored optics and experimental equipment will enable high spatial resolution dichroic spectroscopy, reflectivity and diffraction in combination with extreme pressures, low temperatures and high magnetic fields. Dichroic direct and ptychographic imaging of magnetic structures is being developed and will make use of the largely enhanced coherence of the low emittance source. We present an overview of the planned instrumentation and the upcoming new exciting possibilities.